Gestión administrativa para la optimización del talento humano del circuito Aláquez. Joseguango Bajo. Diseño de un manual de procedimientos para la administración. - Rocha R., Martha Elena (2016)
This research work is based on the subject Administrative Management for optimization of human talent circuit Aláquez - Joseguango Bajo, Design of a procedures manual for administration, seeks to solve the problem of how affects the Administrative Management in the optimization of human talent? For which has been raised as a general objective strengthen administrative management through the optimization of human talent by designing a manual of administrative procedures in the circuit, the methodology used for the development of the research is a quantitative approach, under the documentary literature mode and field, with general and particular methods that allowed the effective systematization of information and the collection and analysis of data, based on the hypothesis that the optimization of human talent affects the administrative management of the educative circuit, generating as a conclusion that: the Administrative Management developed by the educational circuit maintain serious deficiencies in autonomy and communication of educational institutions.